ChemInform Abstract: PtI2‐Catalyzed Cyclization of 3‐Acyloxy‐1, 5‐enynes with the Elimination of HOAc and a Benzyl Shift: Synthesis of Unsymmetrical m‐Terphenyls. Issue 32 (August 2015) - Huang, Kaimeng; Ke, Xiaona; Wang, Hongkai; Wang, Junying; Zhou, Chenchen; Xu, Xiufang; Liu, Lingyan; Li, Jing
Abstract The utility of the method is exemplified by the preparation of a photoelectrically interesting multiphenyl compound [cf.